Generic Programming IFIP TC2 / WG2.1 Working Conference Programming July 11–12, 2002, Dagstuhl, Germany - Gibbons, Jeremy; Jeuring, Johan (IFIP Advances in Information and Communication Technology, 2003)
Generic programming is about making programs more adaptable by making them more general. Generic programs often embody non-traditional kinds of polymorphism; ordinary programs are obtained from them by suitably instantiating their parameters. In contrast with normal programs, the parameters of a generic program are often quite rich in structure; for example, they may be other programs, types or type constructors, class hierarchies, or even programming paradigms. Generic programming techniques have always been of interest, both to practitioners and to theoreticians, but only recently have generic programming techniques become a specific focus of research in the functional and object-oriented programming language communities. Generic Programming comprises the edited proceedings of the Working Conference on Generic Programming, which was sponsored by the International Federation for Information Processing (IFIP) and held in Dagstuhl, Germany in July 2002. With contributions from leading researchers around the world, this volume captures the state of the art in this important emerging area